2011
DOI: 10.2215/cjn.10041110
|View full text |Cite
|
Sign up to set email alerts
|

Icodextrin Increases Technique Survival Rate in Peritoneal Dialysis Patients with Diabetic Nephropathy by Improving Body Fluid Management

Abstract: SummaryBackground and objectives There are still controversies whether peritoneal dialysis (PD) with icodextrin preserves residual renal and peritoneal membrane functions in patients with diabetes. However, there are no randomized controlled and long-term clinical trials in newly started PD patients with diabetic nephropathy.Design, setting, participants, & measurements Forty-one patients with diabetic nephropathy with ESRD were enrolled and randomly assigned to the glucose group (GLU) treated with 8 L of 1.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 24 publications
2
72
0
Order By: Relevance
“…Some patients may be hypovolemic and have a repercussion on RRF, but initial urine volume in the High tertile group was greater than the ultrafiltration volume. There were no significant difference among the tertiles, but there was an increasing trend in the edema index as the tertile of proteinuria level increased Takatori et al showed that urine volume significantly decreased in the earlier period in patients using icodextrin compared with those using glucose solution; however, there was no significant difference between the two groups [31]. They also suggest that superior ultrafiltration may reduce the RRF if the duration of dialysis therapy is >2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may be hypovolemic and have a repercussion on RRF, but initial urine volume in the High tertile group was greater than the ultrafiltration volume. There were no significant difference among the tertiles, but there was an increasing trend in the edema index as the tertile of proteinuria level increased Takatori et al showed that urine volume significantly decreased in the earlier period in patients using icodextrin compared with those using glucose solution; however, there was no significant difference between the two groups [31]. They also suggest that superior ultrafiltration may reduce the RRF if the duration of dialysis therapy is >2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were randomized to 8 L of 1.5% or 2.5% glucose solution or to 1.5 or 2.0 L of 7.5% icodextrin-containing solution. 38 Their results demonstrated that technique survival was 71.4% in the icodextrin group compared to 45.0% in the glucose-containing group, with most of the technique failure due to volume overload. Declines in urine volume and RRF were not signifi cant, even though they appeared to be greater in the icodextrin group.…”
Section: New Osmotic Agentsmentioning
confidence: 98%
“…A more recent randomized open-label trial enrolled 41 incident PD patients with diabetic nephropathy and assigned them to either an icodextrin or dextrose long dwell [18]. The technique survival rate was 71.4% in the icodextrin group and 45.0% in the dextrose group, with most of the technique failure due to volume overload.…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…The long-term implications of these findings on clinical outcomes and peritoneal membrane structure and function are unclear. While data on technique failure was lacking in the meta-analyses described above, one recent trial and Korean registry study suggest that icodextrin may increase technique survival rates [18,19]. More data will be needed to confirm these encouraging preliminary findings.…”
Section: Introductionmentioning
confidence: 99%